On the diverse utility of Cu doped ZnS/Fe3O4 nanocomposites - Shirin Kalantari; Ali Shokuhfar (Scientific Reports)
Abstract The global water crisis is a growing concern, with water pollution from organic dyes being a significant issue. Photocatalysis has emerged as a sustainable and renewable method for removing organic pollutants from wastewater. The study synthesized innovative (2.5, 5 and 10 wt%) Cu doped zinc sulfide/iron oxide nanocomposites using a sonochemical method, which have versatile applications in adsorption and photocatalytic degradation of organic pollutants in wastewater. The nanocomposites underwent comprehensive characterization using powder X-ray diffraction, fourier-transform infrared spectroscopy, photoluminescence spectroscopy, Ultraviolet–Visible spectrophotometer, field emission scanning electron microscopy combined with energy dispersive X-ray spectroscopy and Mott–Schottky analysis. The synthesized samples demonstrate strong adsorption ability to remove RhB and MB dyes. Afterward, we evaluated their capability to degrade Rhodamine B (RhB) dye under UV light exposure. The greatest photocatalytic efficiency was noticed when employing a UV-C lamp in combination with the 10 wt% Cu doped ZnS/Fe3O4 nanocomposite as photocatalyst (98.8% degradation after 60 min irradiation). The Langmuir–Hinshelwood model can be used to describe the pseudo first order kinetics of RhB dye photodegradation. The calculated ban gap values are 4.77, 4.67, and 4.55 eV, for (2.5, 5 and 10 wt%) Cu doped ZnS/Fe3O4, respectively. Furthermore, 10 wt% Cu doped ZnS/Fe3O4 showed good recyclability, with a degradation rate of 89% even after five cycles. Consequently, prepared samples have outstanding photocatalytic activity and can be used as useful adsorbents in water purification.